Association of mixed polycyclic aromatic hydrocarbons exposure with hearing loss and the mediating role of blood cell markers of inflammation in U.S. adults - Shen, Peixuan; Hu, Dan; Shen, Meiyue; Du, Tingwei; Zhao, Longzhu; Han, Miaomiao; Song, Ruihan; Guo, Rongrong; Lu, Xiaochuan; Liu, Shengnan; Shen, Xiaoli (Frontiers in Public Health, 2024)
IntroductionStudies on the effects of polycyclic aromatic hydrocarbons (PAHs) on hearing loss (HL) are limited and often focus on individual PAH compounds. The present study aimed to explore the individual and combined effects of PAH exposure on hearing loss, with a focus on the mediating role of inflammatory blood cell markers.MethodsThis cross-sectional study included 1,409 participants from 3 cycles of the National Health and Nutrition Examination Survey (2001–2002, 2003–2004, and 2011–2012). Seven monohydroxylated PAH metabolites (OH-PAHs) in the urine were measured. Multivariable logistic regression, weighted quantile sum (WQS) regression, and Bayesian kernel machine regression (BKMR) were applied to assess both the individual and combined effects of OH-PAHs on hearing loss. Moreover, mediation analysis was employed to examine the mediating role of inflammatory blood cell markers in these associations.ResultsAmong the 1,409 participants, 59.1% had hearing loss. The WQS model revealed a positive association between PAH mixtures and HL (OR: 1.290; 95% CI: 1.042, 1.597), LFHL (OR: 1.363; 95% CI: 1.130, 1.644), and HFHL (OR: 1.299; 95% CI: 1.022, 1.626). Additionally, the WQS model identified hydroxynaphthalene (1-OHNAP) primarily contributed to HL and LFHL, while 2-hydroxyfluorene (2-OHFLU) was the primary contributor to HFHL. BKMR analysis demonstrated positive associations between PAH mixtures and all three types of hearing loss. Mediation analysis revealed that the association between OH-PAHs and LFHL was mediated by neutrophil (NEU) and basophil (BAS) counts.DiscussionThese results confirmed that exposure to PAH mixtures was positively associated with the odds of hearing loss and that inflammatory blood cell markers mediated this association.